Analysis of the incompatibility determinants of I-complex plasmids. - Nikoletti, S (1988)
The isolation and characterization of minireplicons corresponding to group B and I-complex plasmids are reported. The molecular structures of the small RNAs that may play a major role in the replication control and incompatibility reactions of the plasmids are compared. A mutant plasmid with changed copy number and incompatibility specificity is described. This mutant had a single-base-pair substitution in the DNA region that codes for the small RNA.